Virtually Christian: how Christ changes human meaning and makes creation new - Bartlett, Anthony W. (O-Books, 2011)
Using the seminal anthropology of Rene Girard and drawing out its radical implications Virtually Christian reconfigures the traditional framework of theology. Gone are the heavenly otherworld and its metaphysical God. In their place is revealed a God deeply implicated in the human story and laboring with us for a transformed earth. The identity and mission of Jesus become fully understandable against this background. The consequences for teaching and practice are enormous and especially relevant for emerging church Christians. This book provides a vital contemporary reading of both the gospel